PERMAINAN TRADISIONAL LOMPAT TALI MERDEKA SEBAGAI MEDIA PELAKSANAAN PROSES GAME STAGE DI SD NEGERI 94 PEKANBARU - Tria Paradisa; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The traditional game lompat tali merdeka is a name of traditional game for those who livein Riau Province. The naming of this game has something to do with the movement of playersespecially in the last leap; the rope is stretched by a high-fisted player held up in the air. The fistis almost similar to what the fighters do when they say the word "merdeka". The essence of thegame is jumping ropes that are knotted with graded altitudes. This game is a cooperative gamethat stimulates children to be ready to act (game stage). The method used in this research isdescriptive research method. Descriptive research is research that aims to reveal facts,circumstances, and phenomena. Connected of this research is the disclosure of the game stageprocess and the moral value in the traditional free jump rope game in SD Negeri 94 Pekanbaru.Therefore, the writer will develop concepts, collect data and facts that occur in the place ofresearch. Data collection technique is using qualitative descriptive data analysis techniques fromMiles and Huberman, namely data collection, data reduction, data presentation, and conclusions.Based on the results of the research, in the game there is a stage action process that is the attitudeof players in playing the role in accordance with the status of players. From the game stageprocess, it contains moral values that are not directly visible, but shielded in a symbol when thechild is playing. The moral values are the value of togetherness, simplicity, honesty, leadership,responsibility, stance and obedience rules that are beneficial to develop the soul and shape thechild's character.Keywords: traditional game lompat tali merdeka, game stage, moral values